PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN ADMINISTRASI SISTEM JARINGAN DENGAN MENGGUNAKAN DREAMWEVER - M. Kamal; Ahmaddul Hadi (Universitas Negeri Padang, 2019)
A learning media is made aiming to deliver in delivering teaching materials that will be taught to students in that class, thus the learning techniques that are carried out must be in the form of interesting media in order to provoke students to be more personal and group to be studied by these students . this interactive learning media, offers convenience in learning a learning material because it is packaged in the form of an attractive web display and is very easy to open locallyhost or use the internet and the display also contains material in the form of text, images, animation and video tutorials according to subjects and easily understood by students that the appearance of this media can also be accessed using a browser application that we often use. because there is an interactive web, students are easier to impart information personally in the subjects studied and thus this web can make student motivation increase in learning, because the material contained in this web is in the form of animated beetles that move when clicked on the part that has been given the order and also on this web site there is a stingy tutorial video that is easy for students to understand. The various objectives of a web learning media can form a result or a product that is a learning media site that can trigger learning interest and at the same time facilitate educators in delivering predetermined learning materials such as the K13 curriculum. this product has been implemented feasibility by two media expert lecturers averaging 0.83 and one material expert teacher with an average yield of 0.90 good with the Aiken 'V formula Keywords: learning, interactive, web media